FEATURES OF THE PHARMACOEPIDEMIOLOGICAL DESCRIPTION OF POST-COVID-19 AHAB IN WOMEN - Boltaboev A. M.; Mamasaliev N. S.; Tursunov X. X.; Mamasaliev Z. N.; Boltaboeva D. I. (The Conference Hub, 2025)
Currently, there is very little information on the epidemiology, clinical features, prevention and treatment of Post-Covid-19 Associated Gastrointestinal Diseases (Post-Covid-19 Associated Gastrointestinal Diseases) and none at all in Uzbekistan and, in particular, in the Fergana Valley. According to the scientific results obtained in clinical trials, there is every reason to believe that patients with digestive system diseases may be a risk group for severe disease and unfavorable prognosis when infected with the SARS-CoV-2 virus. [1].